Solid Waste Management from the Perspective of the Right to a Healthy Environment: Progress and Challenges in Peru, Mexico and Chile - Paredes, Julissa Mozombite; Bartra, Martín Pinchi (Journal of Ecohumanism, 2024)
This research work contemplates the reality that is being experienced regarding the management of solid waste in Peru, Mexico and Chile from a legal perspective, related to the fundamental value of the right to a healthy environment. It is argued that the progress achieved with the proper use of solid waste, the management of such advances has been positive or has remained only in documents prepared by the public management for a better management of solid waste and contemplate a better panorama of the law. To this end, the documentation of policies and reports of the problems that persist over time regarding the proper use of solid waste in three Latin American cities such as Lima, Mexico City and Santiago de Chile is analyzed; and, consequently, relate the effect of these documents to improve the relationship of the fundamental right to a healthy environment, constitutionally protected by the laws of the cities in question. Likewise, the constitution that gives the importance of promoting a call to all citizens and authorities in order to achieve the long-awaited sustainable development for the common good of people and the environment in which they live.